Estudo e implementação de um circuito com entrada universal para acionamento de lâmpadas de LED em iluminação residencial - Scarmocin, Jean Carlos (2019)
This work presents the study and implementation of a driver circuit for LED bulbs. Some basic concepts regarding the LEDs and their activation are initially presented, as well as some standards and practical recommendations concerning their existing drive activation modes. The study focuses on the buck-boost converter, since when in continuous drive mode it operates as a power factor pre-regulator. The design and modeling of the converter to be implemented is also presented, as well as the controller, whereas the circuit must operate in closed loop, in order to keep the current in the LEDs constant. The circuit is designed to meet the standards and practical recommendations presented. Next, the design calculations are validated by computer simulation. Finally, the circuit is implemented in printed circuit boards and the results are compared to those obtained through simulation. The experimental results obtained in open and closed loop were satisfactory, meeting the harmonic content standards of the input current IEC 61000-3-2. The output current flicker did not exceed 7.33%, in compliance with IEEE Std 1789-2015 Practical Recommendation 2. In closed loop, the worst efficiency of the converter was 90.9%, the lowest power factor was 0.9878 and the highest harmonic distortion rate was 13.61%.